2017
DOI: 10.1016/s1470-2045(17)30202-4
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer: a disease of the young?

Abstract: As the global burden of non-communicable diseases continues to exert its toll, the prevention, screening, and early diagnosis of cancer should be a priority for all countries. This month, The Lancet Oncology publishes an open letter to Baroness Scotland, Secretary-General of the Commonwealth of Nations. The letter, cosigned by eminent experts in cancer and population health, demands that issues surrounding cervical cancer and endemic childhood cancers are part of the Commonwealth Health Ministers meeting in Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…We explored similarities in expression using DEGs that were identified in more than 80% of tumors for clustering, and up- and downregulated genes were used separately ( Figures 2A–C ). Among these studied tumors, some of them with similar expression dysregulation features clustered together, such as COAD and READ were clustered together, probably because they both belonged to colorectal cancer (CRC) ( The Lancet Oncology, 2017 ), while UCS, OV, and UCEC, which are uterine and ovarian cancers, clustered together.…”
Section: Resultsmentioning
confidence: 99%
“…We explored similarities in expression using DEGs that were identified in more than 80% of tumors for clustering, and up- and downregulated genes were used separately ( Figures 2A–C ). Among these studied tumors, some of them with similar expression dysregulation features clustered together, such as COAD and READ were clustered together, probably because they both belonged to colorectal cancer (CRC) ( The Lancet Oncology, 2017 ), while UCS, OV, and UCEC, which are uterine and ovarian cancers, clustered together.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we demonstrated the associations between the MMP-11 SNPs and CRC. The incidence of CRC is typically low at ages younger than 50 years but strongly increases with age [ 6 , 42 ]. Although the incidence of early-onset CRC (EOCRC) patients, referring to those individuals younger than 50 years, has been rapidly rising over the last 20 years [ 43 , 44 , 45 ], the median age at diagnosis of CRC is about 70 years in developed countries [ 6 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of colorectal cancer is closely related to the growth of polyps, and tumors evolved from polyps are the main cause. The polyps can be divided into three types: proliferative, adenomatous and inflammatory [ 8 , 9 , 10 , 11 ]. The conventional treatment of colorectal cancer is based on surgical resection in the early stage and chemical and/or radiotherapy may be combined according to the condition of the disease.…”
Section: Immunotherapy Of Colorectal Cancermentioning
confidence: 99%